Ethiopia Oil and Gas Sector Development : Support for Review and Update of Policy and Regulatory Framework - World Bank (World Bank, Washington, DC, 2016)
The oil and gas sector in Ethiopia, currently at a very early stage of development, shows good potential for development on the long-run. The sector will benefit from strategies and policies to implement the broader vision for the sector. Development of the oil and gas sector in Ethiopia has the potential to transform the country’s economy. To this end, the Government of Ethiopia (GoE) has requested technical assistance and capacity building support from the World Bank as part of a wider package of support provided by the Bank (in coordination with other development partners) to develop the extractive industries (oil, gas, and mining) sector of Ethiopia. The main objective of the work to be undertaken, is to provide guidance and build capacity in GoE as it undertakes the wider update of its policy, legal, and regulatory framework of the oil and gas sector. Adam Smith International (ASI) was contracted to review the policy and regulatory framework for the oil and gas sector and provide recommendations. This final report on policy and regulatory options has been prepared at the conclusion of the analytical stage of the project, and was preceded by the initiation report submitted in July 2015. This report has two objectives. Firstly, to provide a comprehensive review of the current policy of the GoE towards the oil and natural gas sector. Secondly, to evaluate the regulatory framework in terms of good international practice.